Integrated transfer function for buffeting response evaluation of long-span bridges. Issue 189 (June 2019) - Su, Yi; Li, Mingshui
Abstract: An experimental approach to the prediction of the buffeting response of long-span bridges is presented, and the concept of the integrated transfer function, which directly relates the fluctuation characteristics of turbulent flow to the buffeting response of bridge structures, is introduced in this paper. The integrated transfer function is independent of the characteristics of turbulent flow, so once the integrated transfer function is identified in wind tunnel experiments, it can be directly used to calculate the buffeting response of the actual bridge in the atmospheric boundary layer. To verify the presented approach, a long-span suspension bridge is taken as an example and a series of experiments are carried out in a wind tunnel. Experiments in two different flow fields at the design wind velocity are performed to investigate the effects of turbulent flow characteristics on the integrated transfer functions, and the results measured at another wind velocity are given for comparison. The results show that the integrated transfer functions of the bridge measured in the two flow fields are almost identical, which confirms that it is independent of the flow field. An application example is also performed to evaluate the buffeting response with the use of the measured integrated transfer functions. Compared to the traditional approach, the presented experimental approach based on the integrated transfer function avoids errors caused by the inaccurate simulation of the turbulent flow (such as the integral scales, wind spectra and wind spatial correlations) and provides a more accurate prediction of the buffeting response of long-span bridges. Highlights: The concept of the integrated transfer function for the buffeting response of bridge structures is introduced. An experiment-calculation approach to the prediction of the buffeting response of long-span bridges is proposed. A thought to predict the buffeting response of long-span bridges with section model experiment is provided.